Desarrollos de la teoría de los estratos de Nicolai Hartmann en la psicoterapia de Viktor Frankl - Dalmasso, Mateo (2004)
This paper shows that Nicolai Hartmann’s stratified theory of real world is the main philosophical fundament of Viktor Frankl’s Logotherapy in respect to their fundamental principie: independence in spite of dependence. From this theory Frankl outlines a stratified theory of sicknesses which would end with the many “ism" in anthropological and, above all, psyquiatrical theories. Stratified structure and perspective, which has their source in that, is one of the ways to understand better the real world.